Towards a Resilient City: Analyzing Semarang Preparedness in Facing Disaster Related to Climate Change, Indonesia - Aprillia Findayani; Rahma Hayati; M Fikri Amrullah; Atta-Ur Rahman (Universitas Negeri Gorontalo, 2024)
Semarang, a populous Indonesian coastal city, faces rising sea levels, tidal floods, and potential increases in rainfall intensity due to climate change. Measuring urban resilience is crucial to understand current and future disaster risks, informing the development of effective climate and disaster resilience policies. This study analyzes Semarang City's preparedness for climate-related disasters using a qualitative approach. Focus group discussions (FGDs) and surveys involving stakeholders and representatives from each sub-district were conducted. The Climate Disaster Resilience Index (CDRI) framework was employed to assess preparedness across natural, social, economic, institutional, and physical dimensions. The findings reveal that preparedness in Semarang is a multi-faceted and ongoing effort. While initial analysis suggests a moderate level of preparedness, areas for improvement include strengthening the climate action plan, expanding early warning system reach, and enhancing community flood coping capacity. These actions are essential to safeguard society and the environment, bolstering the city's resilience and adaptability to climate change impacts.